Spatiotemporal optical injection in laser-plasma accelerators - Archer, E (2024)
Laser-driven plasma wakefield accelerators (LWFAs) can accelerate charged particles to multi-gigaelectron volt energies over several centimetres due to the strong electric fields sustained in a plasma. Compared to conventional machines, which are often metres to kilometres-long, plasma-based accelerators have the potential to be the next generation of accelerators for particle physics research, in addition to providing convenient and cost-effective sources of high-energy electrons and radiation for applications in medicine, biology, chemistry and security. To be viable, there are challenges that remain to be addressed, particularly regarding the methods used to inject the witness electrons to be accelerated.